ANALYSIS OF THE TECHNOLOGICAL BALANCE OF PAYMENTS IN SELECTED ARAB COUNTRIES - Hayat Jumaah Mohammed (Scholar Express Journals, 2023)
Some Arab countries are moving in accordance with WTO principles in the liberalization of the foreign trade sector and the liberalization of trade in Globalization goods and services, as production and service activities seek to take into account developments in areas (techno-scientific) such as innovations and ICT, thus forming the foundation of the enabling environment to activate the impact of technological knowledge in stabilizing the dynamics of the technological balance of payments through foreign trade in knowledge products, in order to regulate the returns of the knowledge economy sector, as the trend towards a knowledge-based economy has become a major impact on all Economic sectors as leverage to maximize productivity and economic growth. The research thus involves analyzing and assessing the efficiency of the technological balance of payments performance in selected Arab countries, which has reached the following conclusion of the low efficiency of the performance of qualitative indicators, particularly high, medium and low technological exports, which has exacerbated the technological balance of payments deficit as a result of reduced spending on education, research, development and innovation sectors as a proportion of GDP and a share of government spending. The research recommended that technology sector markets should be freed from monopolistic pressures and the tendency to promote competition in order to provide low-priced technological services by increasing spending on education, research, development and innovation sectors and strengthening public-private partnerships and civil society institutions
Keywords: Technological balance; Education; Globalization goods